Levels of Patient Satisfaction Regarding Healthcare Services in Upazila Health Complexes - Chowdhury, Sayeda Mukta; Islam, ANM Shamsul; Rahman, Md Raziur; Al Zabir, Mollah; Khan, Sara; Azizi, Shajeda; Nurunnabi, Mohammad (Eastern Medical College Journal, 2023)
Background: Patient satisfaction always influences a person to estimate the quality of their healthcare experiences and maintains a continuous relationship with the physicians. The scope of healthcare services varies from country to country. Methodology: A hospital-based cross-sectional study was conducted to assess the levels of patient satisfaction regarding healthcare services among the 202 patients in the purposively selected Upazilla Health Complexes (UHCs) located in Dhaka, Bangladesh. Results: The mean age of the service receivers was 38.88±12.48 years, more than half (56.9%) were homemakers and had no formal education (32.7%), and they came from lower-income families (83.7%). Two-thirds (65.8%) of the patients have received services from OPD. Above half of the patients (59.0%) were satisfied with the services of the UHCs. The satisfaction with doctors was statistically significant with patient occupation and family income; satisfaction with nurse’s services was significant with patient’s education, occupation, and family income; satisfaction with paramedic services was significant with patient’s age and family income. Satisfaction about treatment, cleanliness, environment, and health services of the UHCs were significant with education. Satisfaction with investigation services was significant with education and family income. The patient’s occupation was also significant with the levels of patient satisfaction. Conclusion: To improve the patient satisfaction proper attention should be given to the cleanliness of the UHCs and informing people about all the services of the UHCs. Eastern Med Coll J. July 2023; 8 (2): 31-38